Convergence in the Practice of Legal Aid to Improve Access to Justice. (January 2019) - Sood, Saurabh
This essay locates legal aid as an opportunity to realize the need to improve access to justice in India by converging state and non-state practices of legal aid. Its relevance is argued through the socialism-inspired welfare mandate of the Indian state and well-established constitutional prescription to promote equality of opportunity. In doing so, it asks whether increase in access to justice for the marginalized sections in the society can be achieved through the convergence of the legal service authorities, law schools and non-governmental organizations (NGOs) wherein convergence has been defined as the joint effort of the above-mentioned actors to conduct an event/programme or any activity that falls under the purview of legal aid. To generate evidence on the same, I employ the text analysis technique on data obtained from the quarterly publication of National Legal Services Authority (NALSA) called Nyayadeep . Results show that such convergence is a possibility within the current policy framework. The geographical spread of converging activities is highly concentrated, with a reported increase in collaborative engagement in 2016 from 2015. Public legal education is found to be the most frequently occurring theme on which convergence occurs. This exploratory work addresses the critical gap of literature on the nature of interaction between policy actors in the domain of practice of legal aid and highlights research needs that may inform further work on the topic.